1983
DOI: 10.1190/1.1441409
|View full text |Cite
|
Sign up to set email alerts
|

Self‐potential modeling from primary flows

Abstract: This paper discusses a new method for the investigation of self potentials (SP) based on induced current sources. The induced current sources are due to divergences of the convection current which is driven, in turn, by a primary flow, either heat or fluid. As a result of using this approach there is a shift in emphasis toward the vector flow field and its interaction with current cross‐coupling structure when compared with the total potential approach of Nourbehecht (1963) which emphasized the primary flow po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
172
0
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 291 publications
(186 citation statements)
references
References 12 publications
1
172
0
5
Order By: Relevance
“…This ability is due to the fact that porewaters generally have an excess of electrical charge due to the electrical double layer at the interface between the solid matrix (in this case snow grains) and porewater. The advective drag of this excess of electrical charge is responsible for a streaming current, whose divergence generates a quasi-static electric field known as the streaming potential (Sill, 1983;Revil et al, 2003). More recently, streaming potential theory has been extended for unsaturated conditions Revil et al, 2007;Jougnot et al, 2012).…”
Section: S S Thompson Et Al: Bulk Meltwater Flow and Liquid Water mentioning
confidence: 99%
“…This ability is due to the fact that porewaters generally have an excess of electrical charge due to the electrical double layer at the interface between the solid matrix (in this case snow grains) and porewater. The advective drag of this excess of electrical charge is responsible for a streaming current, whose divergence generates a quasi-static electric field known as the streaming potential (Sill, 1983;Revil et al, 2003). More recently, streaming potential theory has been extended for unsaturated conditions Revil et al, 2007;Jougnot et al, 2012).…”
Section: S S Thompson Et Al: Bulk Meltwater Flow and Liquid Water mentioning
confidence: 99%
“…Equations governing the flow of two immiscible fluids through a porous medium and the coupled equations describing the resulting (low-frequency component of) streaming potential are described in Saunders et al (2008) and elsewhere (e.g., Aziz and Settari (1979);Sill (1983). We assume that the wetting phase (subscript w) is NaCl brine, the nonwetting phase (subscript nw) is a nonpolar oil, that only the wetting phase contributes to the streaming potential and we neglect the contribution of the electric double layer at the fluid-fluid interface.…”
Section: Governing Equationsmentioning
confidence: 99%
“…The streaming-potential coupling coefficient C (V Pa −1 ) is the macroscopic petrophysical property which relates fluid and electric potential gradients (Sill, 1983). It is well-known that the magnitude of the coupling coefficient decreases with increasing brine salinity and, based on data available at the time, Saunders et al (2008) predicted that the streaming potential measured during production may become too small to resolve (<0.1 mV) if the salinity of the formation brine is higher than that of seawater, c. 0.6 mol · L −1 .…”
Section: Introductionmentioning
confidence: 99%
“…A flux of efficient meteoric water is imposed at the ground surface. Following Sill [1983], we first solved the steady‐state equation for the hydraulic head h ( x , z ) with the appropriate boundary conditions (given below) and the distribution of the hydraulic conductivity K ( x , z ). Then, the right‐hand side of the Poisson equation for the electrical potential is computed with a given distribution of the current coupling coefficient L ( x , z ).…”
Section: Numerical Simulationsmentioning
confidence: 99%
“…SP signals correspond to the passive measurement at the ground surface of the electrical potential distribution resulting from polarization processes at play in the ground. The flow of groundwater is responsible for a polarization mechanism known as the streaming potential [ Sill , 1983]. Previous works [ Lange and Barner , 1995] have shown that water‐saturated caves are responsible for positive SP signals at the ground surface while air‐filled caves are responsible for negative SP anomalies.…”
Section: Introductionmentioning
confidence: 99%